Determination of Seven Kinds of Trace Elements in Different Organs of Beijing Black Pig - Zhang, Chun-Jiang; Chen, Wen-Hua; Zhao, Yan; Qiao, Xiao-Ling (Asian Journal of Chemistry, 2012)
Beijing black pig is a specialty in Beijing, but the contents of its meat and organs are still unknown. The muscle, liver and kidney were sampled in Beijing market and determined the contents of seven kinds of trace elements (Zn, Cu, Mn, Pb, Cd, Cr and Fe) by ICP-MS. The recoveries ranged from 90.4-106.3 %, limits of detection range from 0.02-0.23 ng mL-1 and relative standard deviations (RSD) range from 1.5-5.2 %. The results showed that the contents of beneficial elements Zn, Cu, Mn, Fe in liver of Beijing black pig were mostly much higher than that in common pig, the contents of Cd and Pb in meat of Beijing black pig were lower than that in common pig from Qinghai province, so Beijing black pig is a nutritious food. As for different organs, the contents of beneficial elements and heavy metals in different organs are all significantly different, the descending order is liver > kidney > muscle, which is consistent to the organs of bovine.